Centrifugal microfluidic platform for single-cell level cardiomyocyte-based drug profiling and screening1. Issue 17 (7th September 2015) - Espulgar, W.; Aoki, W.; Ikeuchi, T.; Mita, D.; Saito, M.; Lee, J.-K.; Tamiya, E.
<x xml:space="preserve">Abstract</x> Single-cell level drug profiling application of isolated single and groups of neonatal rat cardiomyocytes trapped by centrifugal force.